Sarcopenia predicts reduced liver growth and reduced resectability in patients undergoing portal vein embolization before liver resection - A DRAGON collaborative analysis of 306 patients. Issue 3 (March 2022) - Heil, Jan; Heid, Franziska; Bechstein, Wolf O.; Björnsson, Bergthor; Brismar, Torkel B.; Carling, Ulrik; Erdmann, Joris; Fretland, Åsmund A.; Grunhagen, Dirk; Hana, Renato A.; Hohmann, Joachim; Linke, Richard; et al.
Abstract: Background: After portal vein embolization (PVE) 30% fail to achieve liver resection. Malnutrition is a modifiable risk factor and can be assessed by radiological indices. This study investigates, if sarcopenia affects resectability and kinetic growth rate (KGR) after PVE. Methods: A retrospective study was performed of the outcome of PVE at 8 centres of the DRAGON collaborative from 2010 to 2019. All malignant tumour types were included. Sarcopenia was defined using gender, body mass and skeletal muscle index. First imaging after PVE was used for liver volumetry. Primary and secondary endpoints were resectability and KGR. Risk factors impacting liver growth were assessed in a multivariable analysis. Results: Eight centres identified 368 patients undergoing PVE. 62 patients (17%) had to be excluded due to unavailability of data. Among the 306 included patients, 112 (37%) were non-sarcopenic and 194 (63%) were sarcopenic. Sarcopenic patients had a 21% lower resectability rate (87% vs. 66%, p < 0.001) and a 23% reduced KGR (p = 0.02) after PVE. In a multivariable model dichotomized for KGR ≥2.3% standardized FLR (sFLR)/week, only sarcopenia and sFLR before embolization correlated with KGR. Conclusion: In this largest study of risk factors, sarcopenia was associated with reduced resectability and KGR in patients undergoing PVE.